Decision-making value of nuclear dense fine speckled pattern in systemic autoimmune rheumatic disease: trick or treat? - Deng, Chuiwen; Qu, Xiaohui; Cheng, Shaoyun; Zeng, Xiaofeng; Li, Yongzhe; Fei, Yunyun (Annals of the rheumatic diseases, 2020)
[...]we reviewed our clinical data to aid in this discussion. Though specific DFS70 autoantibodies was not detected, we estimated a 60% chance that these 12 patients would be excluded from the diagnosis of SARD according to the published prevalence of DFS70 autoantibodies in DFS pattern.4 Also, Damoiseaux et al demonstrated that the AC-02 of apparent health individuals or patients who do not have SARD may be produced by autoantigens other than DFS70.1 Indeed, studies found that autoantigens MeCP2, c-MYC binding protein, and the mixed lineage leukaemia protein 1 could cause a DFS pattern,5 6 while their clinical association with SARD has not been illustrated. [...]evaluating the clinical decision-making value of anti-DFS antibody should mainly base on the DFS pattern, which is also consistent with the widely accepted rule that screening ANA by IIF will provide more information than detecting the specific autoantibodies alone.1 2 A 4-year follow-up study found that none of the DFS-positive patients develop autoimmune diseases,7 constituting a crucial evidence to establish the DFS as exclusion biomarker in SARD. [...]it will take longer period than 4 years to confirm the correlation between DFS and autoimmune disease.